DRESS syndrome: Tricky to diagnose but easy to treat - Jose, Antony; Bhat, Smitha; Kumar, Hemanth (Indian Journal of Case Reports, 2022)
A 27-year-old female presented to us with a short history of fever, jaundice, rash, and worsening hepatic dysfunction subsequent to treatment with intravenous antibiotics and alternative medicine for a urinary tract infection. The eosinophilia, lymphadenopathy, and transaminitis prompted us to consider a diagnosis of Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) which can be fatal if not treated. The patient showed improvement in clinical and laboratory parameters after a course of steroids. This case is presented as DRESS syndrome that can prove rapidly fatal if not diagnosed and treated immediately